COMPARISON OF ADVANCIS SCORES, CIN-RISK, AND NATIONAL CARDIOVASCULAR DATA REGISTRY (NCDR) DATA AS A PREDICTOR OF ACUTE KIDNEY INJURY (AKI) IN ST-ELEVATION MYOCARDIAL INFARCTION (STEMI) PATIENTS UNDERGOING PRIMARY PERCUTANEOUS CORONARY INTERVENTION (PCI) - Welliyani I.F. Siagian, Zainal Safri, Abdullah Afif Siregar, Cut Aryfa Andra, Yuke Sarastri & Harris Hasan (International Journal of Research Science and Management, 2019)
Background: Acute coronary syndrome (ACS) is one of the main problems in the cardiovascular. Acute kidney injury (AKI) is a common complication of critical illness, including acute coronary syndrome. Many factors contribute to the occurrence of AKI in acute myocardial infarction (AMI). The clinical tools for predicting the risk of AKI after AMI have not been available. This study compared the ADVANCIS, CIN-risk, and Cath-PCI National Cardiovascular Data Registry (NCDR) scores in predicting the incidence of AKI in ST-elevation myocardial infarction (STEMI) patients undergoing primary percutaneous coronary intervention (PCI). Methods: This cohort study involved 72 STEMI patients who underwent primary PCI at H. Adam Malik General Hospital Medan from October 2018-October 2019. Variables such as risk factors for coronary heart disease, clinical parameters and laboratory values at admission and evaluation of creatinine levels were examined 48-72 hours after primary PCI. Statistical analysis was performed to assess the ability of these scores to predict the incidence of AKI in STEMI patients undergoing primary PCI. Results: Among 72 patients, there were 25 patients (34.7%) who developed AKI and 47 patients did not develop AKI (65.3%). From these three scores studied, the highest area under curve (AUC) is CIN-risk score, which is 0.806 (95% CI: 0.695-0.916), followed by ADVANCIS score 0.771 (95% CI: 0.644-0.898 ), and NCDR score is 0.769 (95% CI: 0.648-0.889). Conclusion: ADVANCIS, CIN-risk, and NCDR scores can be used to predict the incidence of AKI in STEMI patients undergoing primary PCI with CIN-risk scores having the best values as predictors.